Augmented Reality Media in Human Respiratory System Learning Materials: A Literature Review - Subekti, Ani; Yamtinah, Sri; Salimi, Moh (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Augmented Reality (AR) is a promising learning medium that integrates virtual objects into real environments to support interactive and immersive learning, particularly for abstract topics such as the human respiratory system. This study aims to analyze the characteristics and effectiveness of AR-based learning media through a literature review. A total of 15 peer-reviewed articles published between 2020 and 2025 were systematically analyzed. The review focuses on types of AR media, research designs, educational levels, and their impacts on learning outcomes. The results show that AR media are predominantly developed using Research and Development (R&D) approaches, especially the ADDIE model, and are widely applied at elementary and junior high school levels. AR consistently improves conceptual understanding, learning motivation, critical thinking skills, and spatial visualization. Therefore, AR is recommended as an effective and scalable medium for enhancing science learning, particularly in teaching abstract biological concepts.